Efektivitas Penerapan Sanksi Pidana Atas Tindak Pidana Pemilihan Umum Berdasarkan Undang-undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum - Yoga Saprudin Juliansah; Suryana Marta (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2022)
Free and periodic elections have been characterized by a system of democratic states as one of the means for ensuring rights for citizens, there is often a breach in Indonesia's electoral proceedings such as the violation of criminal elections. So the government issued a special bill used to regulate the process of holding elections in 2019, specifically to sanction the perpetrators of the elections violation, using 2017's no. 7 elections. The study adopted the normatif juridical research approach, which normatif's own jurisdiction was a law study that examined written laws from various aspects. This approach approach deals with legal matters based on the normative rules that are associated with the existing circumstances of society. By viewing a case in the public with regard to elections and linking the 2017 rule number 7 of elections for the application of sanctions against the perpetrators of the elections. Legal certainty in the implementation of criminal sanctions against the perpetrators of the general elections under the 2017 rule of elections can be set as an example for the public to avoid committing similar crimes or others, with a sufficient number of cases to be solved. Key words: sanction setting, effective application of criminal sanctions.